Frequency of Grades of Meconium-Stained Liquor and Compare the Frequency of Fetal Outcome according to Grades of Meconium-Stained Liquor - Amina Begum, Shazia Jabbar, Hajira, Aksa Ismail, Sahrish Kanwal, Marvi Bozdar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the different grades of meconium-stained liquor and association of fetal outcome (still birth, poor Apgar score, NICU admissions) among meconium-stained liquor patients according to their grades. Subject and Methods: This prospective case series study was conducted at the department of obstetrics and Gynaecology, civil Hospital Karachi, for 6 months from April 2019 to September 2019. After per vaginal examination meconium-stained amniotic liquor and grades of meconium-stained liquor were confirmed and these patients were monitored by auscultation of fetal heart sounds by pinard stethoscope and cardiotocography performed and when patients delivered, the frequency of fetal outcome according to grades noted and was documented on pre-designed proforma. Results: A total of 150 patient women were studied, their average age was 28.62±4.19 years and mean gestational age was 38.38+1.00 weeks. There 56% multiparous women. Of all meconium-stained liquor, grade II was commonest 40%, grade I 30% and grade III 30%. Still birth was 2.0%, poor Apgar score was 24.7% and rate of NICU admission was 28.0%. Maternal age, parity and gestational age effects were statistically significant on grade of liquor (p-<0.05). Conclusion: Meconium-stained liquor grade II was observed to be high. The adverse fetal outcomes in terms of still birth, low Apgar score and neonatal intensive care unit admission were observed to the significancy associated with meconium-stained liquor grades II and III. Meconium-stained amniotic fluid as a serious problem so early decision should be taken to improve the fetal outcome.